Pelatihan Teknik Penyusunan Presentasi dengan Ms. Power Point Untuk Mahasiswa IKIP Saraswati Tabanan - Ni Made Satvika Iswari; A. A. Istri Ita Paramitha (I-Com: Indonesian Community Journal, 2024)
The ability to use Microsoft PowerPoint is a significant added value for college graduates facing the workforce. IKIP Saraswati, Tabanan, recognizes the importance of this skill and collaborated with Universitas Primakara to conduct training on using Microsoft PowerPoint. This community service activity went through several planning stages to ensure smooth execution. The first stage involved a needs analysis of the partner, followed by pre-implementation coordination. Before the training, a pre-test was conducted to measure the participants' initial abilities. The training, conducted online, covered basic computer system concepts, internet usage, an introduction to Microsoft PowerPoint features, and tips for preparing engaging presentations. The final stage involved a post-test and evaluation to measure the participants' improvement, which proved significant with an average post-test score of 79.24 compared to the pre-test score of 58.15. This training effectively enhanced the participants' knowledge and skills.